Human epidermis models demonstrate mediator role of TLR2 and TLR3 for psoriatic inflammation - Glasebach, Hanna; Denzinger, Lukas; Rupp, Steffen; Burger-Kentischer, Anke (Frontiers in Medicine, 2025)
Psoriasis is a multifactorial systemic autoinflammatory disease that is characterized by complex signaling between keratinocytes and immune cells. The trigger factors for the cutaneous manifestation of the disease are divers but have in common that they induce an activation of the Toll-like receptor (TLR) signaling pathways. This is best described for the activation of TLR7/8/9 in dendritic cells. In this study, we investigated the role of TLR2 and TLR3 activation in keratinocytes for the expression of psoriatic hallmarks in the skin. We set up 3D epidermis models using wild type keratinocytes and TLR2 knockout and TLR3 knockout (KO) keratinocytes derived from the wild type keratinocytes and treated them with TLR agonists. Immunohistochemical, western blot, and multiplex analysis showed that the TLR activation induced the expression of psoriasis associated markers like S100A7, p-STAT3, CXCL-1, IL-8, IL-1α, S100A9, and IL-23 in the wild type but not in the TLR KO epidermis models. Thus, TLR2 and TLR3 activation in keratinocytes individually contributes significantly to inducing the release of cytokines and other immune modulators characteristic for a psoriasis like inflammation in 3D epidermis models.